2000
DOI: 10.3354/meps201147
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and growth of the toxic dinoflagellate Prorocentrum lima and associated fouling macroalgae on mussels in suspended culture

Abstract: We examined the role of substrate interactions and the biological activity of cultured shellfish on the settlement and growth of fouling macroalgae and the toxic epiphyte Prorocentrum lima. Six miniature live-mussel (Mytilus edulis) socks (30 cm long) and 6 dummy socks (created with empty mussel valves) were hung along a horizontal long-line at a sheltered coastal site in Nova Scotia, Canada. After 4 and 9 wk, 3 socks of each treatment were harvested and the biomass of fouling macroalgae and concentration of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 10 publications
4
44
0
6
Order By: Relevance
“…In this study, however, high concentrations of P. lima were found free-living in subsurface waters. In eastern Canada, this species has also been found in substantial concentrations in the water column (Bates, 1997;Lawrence et al, 2000). This species has been frequently found in Mediterranean waters during the last decade (Simoni et al, 2004;Aligizaki et al, 2006;Ingarao et al, 2007).…”
Section: Prorocentrum Lima Prorocentrum Minimum Prorocentrum Sigmoidementioning
confidence: 99%
“…In this study, however, high concentrations of P. lima were found free-living in subsurface waters. In eastern Canada, this species has also been found in substantial concentrations in the water column (Bates, 1997;Lawrence et al, 2000). This species has been frequently found in Mediterranean waters during the last decade (Simoni et al, 2004;Aligizaki et al, 2006;Ingarao et al, 2007).…”
Section: Prorocentrum Lima Prorocentrum Minimum Prorocentrum Sigmoidementioning
confidence: 99%
“…P. lima occurs worldwide in coastal areas, in temperate and tropical oceans and mostly in benthic and epiphytic habitats (Faust et al 1999). In eastern Canada, this dinoflagellate has already been found in substantial concentrations in the water column and attached to vegetation at aquaculture sites in the Miramichi estuary, New Brunswick (Bates 1997), and near Indian Point, Nova Scotia (Lawrence et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…P. lima occurs worldwide in coastal areas, in temperate and tropical oceans and mostly in benthic and epiphytic habitats (Faust et al 1999). In eastern Canada, this dinoflagellate has already been found in substantial concentrations in the water column and attached to vegetation at aquaculture sites in the Miramichi estuary, New Brunswick (Bates 1997), and near Indian Point, Nova Scotia (Lawrence et al 2000).In 1998, 20 people exhibited DSP-like symptoms following the consumption of cultured blue mussels from the Magdalen Islands in the Gulf of St.Lawrence, Canada. The analyses revealed that the mussels contained DTX-1 (no OA), but in too a low concentration to explain the symptoms (0.1 µg g -1 digestive gland; regulatory limit 1.0 µg g -1…”
mentioning
confidence: 99%
“…In fish farm operations, the physical structures of cages and pens create room for the development of fouling macroalgae and other organisms on which P. lima lives and flourishes as an epiphyte (Lawrence et al 2000). Prorocentrum lima can also hang or adhere directly on the structures.…”
Section: Fish Mortalitymentioning
confidence: 99%